Do Explanations Explain? Model Knows Best - Khakzar, Ashkan; Khorsandi, Pedram; Nobahari, Rozhin; Navab, Nassir (Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition, 2022)
It is a mystery which input features contribute to a neural network's output. Various explanation (feature attribution) methods are proposed in the literature to shed light on the problem. One peculiar observation is that these explanations (attributions) point to different features as being important. The phenomenon raises the question, which explanation to trust? We propose a framework for evaluating the explanations using the neural network model itself. The framework leverages the network to generate input features that impose a particular behavior on the output. Using the generated features, we devise controlled experimental setups to evaluate whether an explanation method conforms to an axiom. Thus we propose an empirical framework for axiomatic evaluation of explanation methods. We evaluate well-known and promising explanation solutions using the proposed framework. The framework provides a toolset to reveal properties and drawbacks within existing and future explanation solutions.11https://github.com/CAMP-eXplain-AI/Do-Explanations-Explain
CRIS-Team Scopus Importer:2023-03-08
Keywords: Explainable computer vision